Neuroinflammation in Parkinson's Disease and Related Disorders: A Lesson from Genetically Manipulated Mouse Models of α-Synucleinopathies - Kazunari Sekiyama; Shuei Sugama; Masayo Fujita; Akio Sekigawa; Yoshiki Takamatsu; Masaaki Waragai; Takato Takenouchi; Makoto Hashimoto (Parkinson's Disease)
Neuroinflammation in Parkinson's disease (PD) is a chronic process that is associated with alteration of glial cells, including astrocytes and microglia. However, the precise mechanisms remain obscure. To better understand neuroinflammation in PD, we focused on glial activation in α-synuclein (αS) transgenic and related model mice. In the majority of αS transgenic mice, astrogliosis was observed concomitantly with accumulation of αS during the early stage of neurodegeneration. However, microglia were not extensively activated unless the mice were treated with lipopolysaccharides or through further genetic modification of other molecules, including familial PD risk factors. Thus, the results in αS transgenic mice and related model mice are consistent with the idea that neuroinflammation in PD is a double-edged sword that is protective in the early stage of neurodegeneration but becomes detrimental with disease progression.